2012
DOI: 10.2106/jbjs.k.00888
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Psychopathology on Patient-Perceived Outcomes of Total Knee Arthroplasty within an Indigent Population

Abstract: Not only is there a high prevalence of psychopathology in the indigent population, but psychopathology may result in lower patient-perceived outcome scores at one year after a total knee arthroplasty. Even though outcome scores may be worse for patients with psychopathology, our study showed that these patients still benefit, with the same degree of improvement in function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
64
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 92 publications
(65 citation statements)
references
References 60 publications
1
64
0
Order By: Relevance
“…The remaining six studies did not examine these states specifically but showed that lower preoperative mental health scores had similar postoperative associations [8,9,13,27,46,47,50]. Pain scores in the patient population with anxiety, depression, or lower mental health scores were elevated at baseline and at all assessment points [13,27,28,34,37,47,50] for up to 2 years in one study [34 ]. Lingard and Riddle [34] estimated the effect to be 3 to 5 points lower on the 20-point pain component of the WOMAC, indicating worse pain in the group of patients with lower mental health scores.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The remaining six studies did not examine these states specifically but showed that lower preoperative mental health scores had similar postoperative associations [8,9,13,27,46,47,50]. Pain scores in the patient population with anxiety, depression, or lower mental health scores were elevated at baseline and at all assessment points [13,27,28,34,37,47,50] for up to 2 years in one study [34 ]. Lingard and Riddle [34] estimated the effect to be 3 to 5 points lower on the 20-point pain component of the WOMAC, indicating worse pain in the group of patients with lower mental health scores.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 19 studies, there were 17 cohort studies [3, 5, 8, 9, 13, 14, 24, 26-28, 34, 37, 39, 44, 46, 47, 50] and two cross-sectional surveys [15,18], including five level 1 prognostic studies [3,8,13,34,39]. The studies were conducted in seven countries: 10 in the USA [3,5,8,9,13,14,24,34,39,46]; four in the UK [27,34,44,50]; four in Canada; [18,26,34,47]; and one each in Australia [34], Spain [15], Greece [37], and Korea [28].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations